The Role of Influencer Collaboration as A Marketing Strategy In Promoting New Product Collection: A Case Study of Thenblank X Isyana Sarasvati - Gracia Gunardi (CV. Publikasi Indonesia, 2024)
Internet, social media, mobile apps, and other digital communications technologies have all become a part of everyday life for billions of people around the world. A global phenomenon, as mentioned by Backaler is that influencer marketing is growing in countries around the world. One example of a local fashion brand that has recently just adopted influencer collaboration as its marketing strategy is THENBLANK. The study objectives of this research are to analyze the role of Isyana Sarasvati as a marketing strategy collaborator in promoting THENBLANK’s new product collection, to know how Isyana Sarasvati contributes to THENBLANK’s marketing strategy, and to identify the factors that THENBLANK considers when choosing an influencer to collaborate with. The method used in this research is a qualitative method with semi-structured in-depth interviews as the data collection method. The theories and concepts used in this research are the Stimulus-Response Theory, AISAS Model, Pillars of Influence, and Marketing Strategy. The result of this research shows the collaboration between THENBLANK and Isyana was successful because of the compatibility of personality and character. THENBLANK also collaborates with Isyana because they want to increase the brand value, brand image and social status of customers, and this was in accordance with their selection. The role of Isyana as an influencer is also very good and contributes through making a song scoring, providing criticism and input, and many more.